2004
DOI: 10.30843/nzpp.2004.57.6940
|View full text |Cite
|
Sign up to set email alerts
|

Optimising tine weeding in organic pea crops

Abstract: Field trials were undertaken over three years to determine the effect of tine weeding in organic pea (Pisum sativum) crops in Canterbury The tine weeding treatments were performed either as single or repeated passes at different times of crop growth Significant weed control and yield increase were achieved with a single pass of tine weeding either at preemergence or at the 2leaf stage of the crop On some occasions two passes of tine were required to control new weeds Late postemergence tine weeding did not hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 4 publications
0
16
2
Order By: Relevance
“…Comparing our results with reports based on qualitative experimental approaches, where one or two passes with a harrow are carried out at different growth stages, is not straightforward (Dastgheib, 2004;Ausˇkalnis & Ausˇkalnien_ e , 2008;Pardo et al, 2008;Velykis et al, 2009). To describe a treatment with a cultivator by the number of passes is more or less like describing a herbicidal treatment by the amount of herbicide used without information about the active ingredient.…”
Section: Discussioncontrasting
confidence: 52%
“…Comparing our results with reports based on qualitative experimental approaches, where one or two passes with a harrow are carried out at different growth stages, is not straightforward (Dastgheib, 2004;Ausˇkalnis & Ausˇkalnien_ e , 2008;Pardo et al, 2008;Velykis et al, 2009). To describe a treatment with a cultivator by the number of passes is more or less like describing a herbicidal treatment by the amount of herbicide used without information about the active ingredient.…”
Section: Discussioncontrasting
confidence: 52%
“…Pre-emergence harrowing was very effective against the early emerging tap-rooted species S. arvensis in the field experiment with peas at Enko¨ping in 2003. Koch (1959 reported similar results.…”
Section: Discussionmentioning
confidence: 74%
“…When pre-and post-wh was combined, it was possible to disturb the growth of both types of weed species at their most sensitive developmental stage (cotyledon stage). The importance of weed control timing in this respect was also shown by Dastgheib (2003), who observed that pre-wh in winter wheat sometimes provided satisfactory weed control, but a post-wh was required for late emerging weeds. Rasmussen and Rasmussen (1995) showed that with pre-wh in spring barley a reduction of 61% in weed dry weight was achieved, while a reduction of 74% was achieved when pre-and post-wh was combined.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This study was undertaken to compare different times and numbers of tine weeding in commercially grown organic wheat in central Canterbury. This report follows a previous paper (Dastgheib 2003) and summarises the results from three years of study.…”
Section: Introductionmentioning
confidence: 65%